Microhardness, Surface Roughness, and Wear Resistance Enhancement of Reinforced Conventional Glass Ionomer Cement Using Fluorinated Graphene Oxide Nanosheets - Aboelwafa, Mona R.; Shaheen, Sarah D. (European Journal of Dentistry, 2024)
Objectives Conventional glass ionomer cements (GICs) have been considered the most prevalent restorative material however; the reduced mechanical qualities and decreased wear resistance have been the main challenges facing their wide clinical application. This study was designed to assess the mechanical properties of fluorinated graphene (FG) oxide-modified conventional GIC.Materials and Methods Composites of FG/GIC samples were prepared using (Medifil from PROMEDICA, Germany, shade A3) at different concentrations (0wt%) control group and (1wt%, 2wt% and 3wt% FG) groups using cylindrical molds (3mm × 6mm). FG was prepared using hydrothermal technique and characterized using XPERT-PRO Powder Diffractometer system for X-ray diffraction analysis and JEOL JEM-2100 high resolution transmission electron microscope. Vickers' hardness and wear resistance of GI samples were measured. Mechanical abrasion was performed via three-body tooth brushing wear test using ROBOTA chewing simulator coupled with a thermocycling protocol (Model ACH-09075DC-T, AD-Tech Technology Co., Ltd., Leinfelden-Echterdingen, Germany).Statistical Analysis Comparisons between groups with respect to normally distributed numeric variables were performed using one-way analysis of variance test followed by posthoc test. While paired t-test was utilized for comparing data within the same group.Results: The surface roughness values of GICs (1wt% FG) and (2wt% FG) composites were significantly lower than those of the control and 3wt%FG groups. Vickers' hardness numbers were significantly higher in FG/GICs composites than in the control group (p≤0.05).Conclusion GIC/FG combinations have sufficient strength to resist the occlusion stresses with improved hardness as compared with conventional GIC. GIC/FG appeared to be a promising restorative material.
Keywords: fluorinated graphene oxide; conventional glass ionomer cements; Vickers' hardness numbers